An evaluation of a community living initiative in Ireland. (September 2015) - Sheerin, Fintan; Griffiths, Colin; de Vries, Jan; Keenan, Paul
One of the central principles underpinning Irish intellectual disability policy is that of decongregation. Allied to this is the belief that life in community settings offers greater opportunities and richer experiences than does life in institutional settings. This study explores the experiences of a group of adults with intellectual disabilities who moved from residential settings to living units in the community. Using a qualitative descriptive approach, it considers the significance of that move for them and seeks to understand the extent to which their lives have changed. Whereas it emerges that this was a positive period in their lives, it is clear that a number of issues remain to be addressed and these provide useful information for similar developments in the future.